The central role of CT coronary angiography in postcardiac arrest care in the young adult. Issue 12 (30th December 2019) - Khan-Kheil, Ayisha Mehtab; Moss, Alexandra Sophie; Stephens, Leanne; Khan, Jamal Nasir
Abstract : A 32-year-old man with no medical history went into ventricular fibrillation while running at the gym. He was transferred to our tertiary centre post successful resuscitation where admission electrocardiography and echocardiography were unremarkable. The initial cause of cardiac arrest was suspected arrhythmogenic and he was admitted for further investigations including exercise testing, ajmaline challenge, CT coronary angiography (CTCA) and cardiovascular MRI, with the likely outcome of cardioverter-defibrillator implantation. CTCA, however, revealed significant stenosis in the proximal left anterior descending artery as the likely cause for his arrest. Invasive coronary angiography confirmed this and facilitated successful stent implantation, avoiding the need for implantable cardioverter-defibrillator implantation. This case highlights the importance of CTCA, a non-invasive and readily-available test in the investigation of young patients postcardiac arrest, who require active exclusion of coronary artery disease and anomalous coronary anatomy, though they represent a low-risk population group.